SCAMM: detection and prevention of SQL injection attacks using a machine learning approach - Alam, Auninda; Tahreen, Marjan; Alam, Md Moin; Mohammad, Shahnewaz Ali; Rana, Shohag (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.